Persepsi Nasabah Tentang Implikasi Lending Dan Funding Terhadap Minat Beli Di Bank Syariah - Widyaningsih, Bekti; Rahmatika, Arivatu Ni’mati; Agustin, Zeni Aristiya (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2025)
Consumer Behavior Theory, perception and behavior play an important role in customer decisions to choose banking services. This study aims to analyze customer perceptions of Islamic banking products, especially lending and funding products, and their implications for customer purchasing interest at Bank Syariah Indonesia (BSI) Jombang Branch Office. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to BSI KC Jombang customers, then analyzed to identify the relationship between perception, attractiveness of lending and funding products, and customer purchasing interest. The results of the study indicate that positive perceptions of Islamic Banks significantly increase customer purchasing interest, both in lending and funding products